Open classroom in a closed society: Effects of patriotism and ideological diversity in the Russian school - Efimova, Evgenia (JSSE - Journal of Social Science Education, 2024)
Purpose: This study investigates the relationship between political discussions and ideological composition in the classroom. Design: The effects of class patriotism and within–class differences in it are analysed using the Russian data from the International Civic and Citizenship Education Study. Findings: Students in more patriotic and like–minded classes perceive the classroom climate as more open, but it does not change its effect on knowledge. There is a negative relationship between ideological diversity and civic knowledge. These effects in Russia are neither unique nor the strongest among the ICCS participants. The reality of an open classroom might be far from the idealised notion of balanced deliberation, and its diversity remains a challenge rather than an opportunity. Research limitations and implications: The study makes no claims about the directionality of the relationships due to their correlational nature. More research is needed on the quality of reasoning in social studies classrooms in times of polarisation and political turmoil.